Impact of the early COVID‐19 pandemic on Breast Surgical Oncology fellow education. Issue 7 (30th July 2021) - Kilgore, Lyndsey J.; Murphy, Brittany L.; Postlewait, Lauren M.; Liang, Diana H.; Bedrosian, Isabelle; Lucci, Anthony; Kuerer, Henry M.; Hunt, Kelly K.; Teshome, Mediget
Abstract: Introduction: The early COVID‐19 pandemic rapidly transformed healthcare and medical education. We sought to evaluate the professional and personal impact of the pandemic on 2019–2020 Breast Surgical Oncology (BSO) fellows in Society of Surgical Oncology approved programs to capture the experience and direct future changes. Methods: From July 15, 2020 to August 4, 2020 a survey was administered to the American Society of Breast Surgeons' fellow members. The survey assessed the impact of the pandemic on clinical experience, education/research opportunities, personal health/well‐being, and future career. Responses were collected and aggregated to quantify the collective experience of respondents. Results: Twenty‐eight of fifty‐seven (54%) eligible fellows responded. Twenty‐one (75%) indicated the clinical experience changed. Twenty‐seven (96%) reported less time spent caring for ambulatory breast patients and sixteen (57%) reported the same/more time spent in the operating room. Fourteen (50%) stated their future job was impacted and eight (29%) delayed general surgery board examinations. Stress was increased in 26 (93%). Personal health was unaffected in 20 (71%), and 3 (10%) quarantined for COVID‐19 exposure/infection. Conclusion: The COVID‐19 pandemic altered the clinical experience of BSO fellows; however, the operative experience was generally unaffected. The creation of frameworks and support mechanisms to mitigate potential challenges for fellows and fellowship programs in the ongoing pandemic and other times of national crisis should be considered.